Dainik Bhaskar: live no negative. Issue 3 (31st July 2017) - Parsad, Chandan; Prashar, Sanjeev; Sahay, Vinita
Abstract : Subject area: Strategic Marketing Management. This case is also relevant for discussion in other courses like brand management. Study level/applicability: Postgraduate Management students. Case overview: Just before the official launch of "no-negative" news edition by Dainik Bhaskar Corp. Ltd, there was widespread speculation that the group was risking too much by going against the set convention of the newspaper industry. The common belief in the industry was "If it bleeds, it leads" and "good news is no news". While endeavoring to do away with this perception, the management needed answers to questions like "Would it really be an attractive proposition for the readers?", "Was the group compromising the role and responsibilities of press in presenting the truth to the world?" and "How would it add value to the brand?" The entire debate was pivoted around the sustainability of positive marketing strategy and "Is it a good idea to go forward with No Negative?" For decades, Dainik Bhaskar was known for its strategy of capturing untapped markets or denting into monopolistic markets and become a leader. This case is an odyssey of moving away from the "me-too" to category (positive newspaper) positioning. The main objective of this case is to build the concept and rudiments of positive marketing in practical perspectives using the backdrop of the Hindi newspaper industry and its largest player breaking the myth "only negative news sell". Besides this, the case also evolves the process of institutionalizing positive marketing in organizations. Expected learning outcomes: The primary objective of teaching through this case is to make students aware and understand the emerging strategy of positive marketing and its ability to break through the present clutter in the market. It also elaborates on how companies can use this tool for differentiating themselves from others. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 8: Marketing.